2017
DOI: 10.1016/j.jvs.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of brachial artery-brachial vein arteriovenous fistulas with arteriovenous grafts in patients with poor superficial venous anatomy

Abstract: The BVAVF is a viable alternative to the AVG in patients with inadequate superficial venous anatomy, especially in access-naïve patients. The decision to perform BVAVF must be weighed against the delay in functional maturation expected compared with AVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…3,15,18 In a cohort of patients like ours with no superficial vein, Pham et al reported a comparison of 29 BrVTs with 32 AVGs in the forearm or upper arm. 26 Our BrVT experience shows superior results with 91% (65%) 1-year secondary functional patency compared with 52% for BrVT and 47% for AVG in their recent publication.…”
Section: Discussionmentioning
confidence: 67%
“…3,15,18 In a cohort of patients like ours with no superficial vein, Pham et al reported a comparison of 29 BrVTs with 32 AVGs in the forearm or upper arm. 26 Our BrVT experience shows superior results with 91% (65%) 1-year secondary functional patency compared with 52% for BrVT and 47% for AVG in their recent publication.…”
Section: Discussionmentioning
confidence: 67%
“…The use of the brachial vein for vascular access is not popular among vascular surgeons, but may be a good hypothesis for a permanent autologous access. In the review of the literature, we identified 11 studies, between 2005 and 2017, with a total of 330 brachio‐brachial AVF (1 or 2‐stage) . This type of fistula can be created in 1 or 2‐stage, and it is a viable alternative to the arteriovenous graft in patients with inadequate superficial venous anatomy, especially in access‐native patients .…”
Section: Discussionmentioning
confidence: 99%
“…In the review of the literature, we identified 11 studies, between 2005 and 2017, with a total of 330 brachio‐brachial AVF (1 or 2‐stage) . This type of fistula can be created in 1 or 2‐stage, and it is a viable alternative to the arteriovenous graft in patients with inadequate superficial venous anatomy, especially in access‐native patients . Our solution to drain the cephalic radio veins through the brachial vein may allow the creation of the brachio‐brachial fistula in one stage.…”
Section: Discussionmentioning
confidence: 99%
“…An autogenous arteriovenous fistula using superficial forearm veins is the first choice for hemodialysis access because of its greater patency, lower rate of infection and lower morbidity and mortality. 1,2 The National Kidney Foundation Dialysis Outcomes Quality Initiative (NKF-DOQI) recommends that at least 65% of patients should have an autogenous arteriovenous fistula for access. 3 Chronic kidney disease requiring dialysis is a serious condition with high mortality and its prevalence is growing exponentially in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrated increased patency and lower rates of complications of this type of access over the short and long terms, compared with arteriovenous grafts. 1,9 The objectives of the present study are to evaluate the patency and complications of brachial vein transposition compared with other autogenous accesses using the standard superficial veins and to present this method as an alternative to synthetic prostheses as access for hemodialysis.…”
Section: Introductionmentioning
confidence: 99%